Penyelesaian Sengketa Terhadap Aktivitas Di Ruang Angkasa oleh Pihak Non-Negara (Privat) - Muhammad Havez; Muhammad Insan Tarigan (Fakultas Hukum Universitas Surabaya, 2018)
Recently, there are some complex issues regarding the use of outer space caused by the activities of private role in the outer space activities. One of the significant impacts that caused by private parties in outer space is international dispute settlement mechanism. Therefore, the purpose of this article is to find the international dispute settlement mechanism that can be taken on the cases that involve private parties. This article uses normative legal research, which using library research or secondary data, that consist of primary, secondary, and tertiary sources to answer the legal problems of this research. First, this article will discuss on dispute settlement in context of international law in general. Afterwards, it will be continued by elaborating dispute settlement mechanism in outer space that also involve private parties. There are some of international dispute settlement that mentioned on Article 33 paragraph (1) United Nations Charter, such as negotiation, enquiry, mediation, conciliation, arbitration, judicial settlement, resort to regional agencies or arrangements, or other peaceful means of their own choice. International Court of Justice (ICJ) is one of dispute settlement mechanism that can be use in international law. However, in the reality ICJ only solve dispute that involved state to state, thus dispute that related with private parties in outer space cannot be solved through ICJ. Referring to ITU Convention and Constitution 1992, dispute settlement that involve private parties in outer space can be solved through diplomatic channel and international arbitration.